Evaluation of intramuscular olanzapine and ziprasidone in the medically ill - Seema M. Patel, PharmD, BCPP; Ericka L. Crouse, PharmD, BCPP, BCGP, FASHP, FASCP; James L. Levenson, MD (American Association of Psychiatric Pharmacists, 2021)
Introduction: Despite the paucity of studies evaluating short-acting parenteral second-generation antipsychotics in the medically ill, their use in this population has increased. The purpose of this study was to characterize the use of IM olanzapine and ziprasidone in the medically ill at an academic medical center. Methods: This is a retrospective medical record review of all patients who received IM olanzapine or ziprasidone on nonpsychiatric inpatient units at a large academic medical center from August 1, 2015 to July 31, 2017. The primary endpoint characterized the indication for use. Secondary endpoints included safety, effectiveness, and prescribing patterns. Results: After exclusion criteria, a total of 100 patients were included in this study, predominantly white males with a mean age of 56 years. Seventy-four percent of patients received IM ziprasidone and 26% received IM olanzapine. The most common indications for use were agitation of nonpsychotic origin (40%) and delirium (33%). Patients received IM olanzapine and ziprasidone when their use was contraindicated (26.9% vs 9.5%, respectively). Discussion: Intramuscular second-generation antipsychotics are increasingly being used in the medically ill for delirium and agitation. Our study confirms these were the most common indications for IM second-generation antipsychotic use in this population. Additionally, their use appeared to be well-tolerated, and no patient developed Torsades de Pointes even when combined with other agents that putatively increase QTc. Given the retrospective, single-center, nonrandomized design of this study, the safety and effectiveness of these parenteral second-generation antipsychotics in common causes of acute agitation should continue to be further evaluated.